PENGEMBANGAN BUDIDAYA UDANG VANAME SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DI DESA SEMUT, WONOKERTO, PEKALONGAN - Prayogi, Arditya; Azizah, Alfatull (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2022)
One of the villages in the Pekalongan Regency area which is located on the coast, and has great potential in the fisheries (catch and cultivation) and marine sector, namely Semut Village. Shrimp and milkfish cultivation is a form of aquaculture that is widely developed in this village. In addition, there are also crab catching activities. Community empowerment activities through the use of existing land for the development of vaname shrimp cultivation. This activity lasts 2 months from April to June 2021. The main goal is to improve community skills in the process of vaname shrimp cultivation. Training, both practical and theoretical, was provided mainly in the form of knowledge and technical skills regarding the preparation of vaname shrimp ponds. The community involved in vaname shrimp cultivation activities in Semut Village is the